Sweat analysis device - Akhmed Ebrakhim (Cognum Publishing House, 2020)
There is information about create the device fot sweat analysis. Using the biosensor and the mobile phone and some program it is posible develop the enough simple and usefull device for get information about big numbers different human parameters
Keywords: sweat; analysis